Dayah, Tarekat Alawiyah, dan Kontestasi Praktik Agama di Aceh: Membaca Manuskrip Kaifiat Qulhu - Muhammad, Wildan Imaduddin (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2022)
Kaifiat Qulhu is a manuscript from Dayah Tanoh Abee, located in Seulimeum Aceh Besar, Aceh. The text explains the prayer wheel (wirid) of Q. 112 for self-salvation, parent-salvation and ancestors that referred to tariqa alawiya, especially to Abd Allah b. Alawi al-Haddad (1634-1720). This text was written by Muhammad Ali (d. 1969), eighth generation of Dayah Tanoh Abee, in 1328/1910. Kaifiat Qulhu, which illustrated the construction of religiousity in Tanoh Abee, outlines the character of diversity in Islamic practices and sufi order in Aceh that can be seen in two domains. Firstly, in how the text contains the critique of tahlil tradition to bless the death people that according to the text, it has no argument in hadith. Secondly, in evidence of transmission (ijazah) of tariqa alawiya beside Shattariya that was more popular in Aceh previously. This research finds that the manuscript is construct two things: first, dialectical discourse of tariqa in Aceh and second, the openness of Aceh’s Ulama to the differences.